Wandering spleen: a unique cause of acute abdomen - Lian, Hooi San; Firdaus Hayati; Aishath Azna Ali; Nornazirah Azizan; Mohd Firdaus Che Ani; Muhammad Aznan Suhail; Andee Dzulkarnaen Zakaria (Wydawnictwo Via Medica, 2017)
We present the case of a 16-year-old boy presented with 2-week episode of wor-sening lower abdominal pain. Clinically, there was a tender palpable mass on the suprapubic region. Ultrasonography showed an absent spleen at its usual area, instead suprapubic mass suggestive of ectopic spleen was identified. An emer-gency laparotomy revealed a congested spleen in the pelvic cavity. Splenectomy was undertaken as it was non-viable. The patient was discharged uneventfully with triple vaccinations. We describe this unique entity with its literature review. (Folia Morphol 2018; 77, 2: 400-402).